Sorption Profile of Phosphorus Ions onto ZnO Nanorods Synthesized via Sonic Technique. (11th April 2016) - Elkady, M. F.; Shokry Hassan, H.; Salama, Eslam
Abstract : High surface area zinc oxide material in nanorod morphological structure was synthesized using an ultrasonic technique in the presence of polyvinyl pyrrolidone as stabilizing agent. The crystallite, morphology, and surface area of the prepared white powder material were identified using XRD, SEM, and BET techniques, respectively. X-ray analysis confirms the high purity of synthesized ZnO. The evaluated specific surface area of prepared ZnO was 16.7 m 2 /g; this value guarantees high efficiency for water purification. The feasibility of synthesized ZnO nanorods for phosphorus sorption from aqueous solution was established using batch technique. Nano-zinc oxide exhibits high efficiency for phosphorus removal; the equilibrium state was recorded within 90 minutes. The most effective hydrogen ion concentration of the polluted solution was recorded at pH = 1 for phosphorus decontamination. The equilibrium of phosphorus sorption onto ZnO nanorods was well explained using both Langmuir and Temkin isotherm models. The calculated maximum monolayer sorption capacity was 89 mg/g according to Langmuir isotherm at 27°C. In order to explain the phosphorus sorption mechanism onto the prepared ZnO nanorods, three simplified kinetic models of pseudo-first order, pseudo-second order, and intraparticle diffusion rate models were tested. Kinetics was well fitted by pseudo-second order kinetic model with a contribution of intraparticle diffusion.